PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP PENURUNAN INSOMNIA PADA LANSIA DI PANTI JOMPO YAYASAN GUNA BUDI BAKTI MEDAN 2021 - Raudah Tinnur; Hasrat Ndruru; Eirene Kristiani Waruwu; Putri Anggi Angriani; Arta Manova Doloksaribu; Tiarnida Nababan (STIKes Al-Insyirah Pekanbaru, 2021)
Insomnia is a condition experienced by individuals who wake up or find it difficult to sleep both at night and during the day as a result of physiological changes experienced by the elderly as they age. Lavender aromatherapy is a non-pharmacological therapy to treat insomnia. This study aims to determine the effect of reducing sleep quality problems in the elderly. This type of research uses a pre-experimental design method using a one group pretest-posttest design, the number of samples is 25 respondents and the information collection instrument used is the KSPBJ-IRS questionnaire consisting of 11 questions, as well as filling out the questionnaire at the beginning and at the end which is assisted by researchers to measure the level of insomnia in the elderly carried out for 7 days. The results obtained were statistically processed using the SPSS application through the Pired test. Sample T test was obtained with df 25 p-value 0.200 > (0.005). The results showed that there was an increase before and after the lavender aromatherapy intervention, the conclusion was that there was a decrease in insomnia in the elderly after being given lavender aromatherapy at the Guna Budi Bakti Nursing Home in Medan. It is recommended for the elderly to continue giving lavender aromatherapy with the help of nurses to improve sleep quality.